2017
DOI: 10.1016/j.gaitpost.2016.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Validity and sensitivity of the longitudinal asymmetry index to detect gait asymmetry using Microsoft Kinect data

Abstract: Research highlights:-The Continuous Relative Phase is not useable with Kinect.-New longitudinal index Ilong is sensitive and validated to detect gait asymmetry.-The Ilong index works with Kinect placed either in front of or behind subjects.-Only few strides (at least 5) are needed to compute a valid Ilong. AbstractGait asymmetry information is a key point in disease screening and follow-up. Constant Relative Phase (CRP) has been used to quantify within-stride asymmetry index, which requires noise-free and accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The tools and methodologies used to assess GA are often arbitrary [ 10 ] and often studied in non-natural controlled conditions. Currently available methods include reflective skin markers [ 11 ], ear-worn sensors [ 12 ] and camera based motion analysis systems [ 13 ]. Other methods for measuring GA include ground reaction forces [ 14 ], dynamic electromyography [ 15 ], and instrumented walkways [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tools and methodologies used to assess GA are often arbitrary [ 10 ] and often studied in non-natural controlled conditions. Currently available methods include reflective skin markers [ 11 ], ear-worn sensors [ 12 ] and camera based motion analysis systems [ 13 ]. Other methods for measuring GA include ground reaction forces [ 14 ], dynamic electromyography [ 15 ], and instrumented walkways [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies evaluated the validity and reliability of the Microsoft Kinect v2 skeleton estimation using markerbased motion capture systems as a golden standard system [19]- [27], none of these studies investigated or reported any distortion in the estimated joint positions. The majority of these studies employed Vicon [19], [20], [33], [34], [21], [26]- [32], BTS SMART-DX [22], [35], or Qualisys [24], [36], [37] motion capture systems that all utilize reflective markers. Microsoft Kinect v2 estimates the depth information based on time-of-flight (ToF) principle using infrared (IR) emitters and detector [38].…”
Section: Introductionmentioning
confidence: 99%
“…The recent explosion of ambient sensors (e.g., motion capture sensors, force mats), smart phones, and wearable sensor systems (e.g., inertial measurement units, IMUs) have facilitated the emergence of new techniques to monitor gait and balance control in natural environments and during everyday activities [8,22,29]. Embedded into living environments, ambient third-person video (TPV) and depth cameras (e.g., Microsoft Kinect) have been investigated as means to extract gait parameters [14,10], detect episodes of freezing of gait in Parkinson's disease [5], detect falls, and longitudinal changes in the patient's mobility patterns [4,36,3]. While TPV systems have demonstrated potential to detect small changes over long periods (i.e., months to years), these approaches suffer from visual occlusions (e.g., furniture), difficulty handling multiple residents, and extraction of spatiotemporal parameters when the full-body view is unavailable.…”
Section: Introductionmentioning
confidence: 99%